(2x+5)=(7x-15)

Simple and best practice solution for (2x+5)=(7x-15) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2x+5)=(7x-15) equation:


Simplifying
(2x + 5) = (7x + -15)

Reorder the terms:
(5 + 2x) = (7x + -15)

Remove parenthesis around (5 + 2x)
5 + 2x = (7x + -15)

Reorder the terms:
5 + 2x = (-15 + 7x)

Remove parenthesis around (-15 + 7x)
5 + 2x = -15 + 7x

Solving
5 + 2x = -15 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
5 + 2x + -7x = -15 + 7x + -7x

Combine like terms: 2x + -7x = -5x
5 + -5x = -15 + 7x + -7x

Combine like terms: 7x + -7x = 0
5 + -5x = -15 + 0
5 + -5x = -15

Add '-5' to each side of the equation.
5 + -5 + -5x = -15 + -5

Combine like terms: 5 + -5 = 0
0 + -5x = -15 + -5
-5x = -15 + -5

Combine like terms: -15 + -5 = -20
-5x = -20

Divide each side by '-5'.
x = 4

Simplifying
x = 4

See similar equations:

| 38=p-12 | | 2a+5a=49 | | 3g-7+5g=1 | | 2x/3-3x/5=8 | | 5x-6z=17 | | 2x+17=4x+5 | | 2(4b-3)=8b-6 | | 2x-15+4x=180 | | 5d+9+2+2d= | | x+3x+6=46 | | -2b-14=-(5b+2) | | 5(5n+3)=14n-29 | | -1-7x+3x=39 | | (4y+24)=(7y+3) | | -3y-y+8=6y-5y+18 | | 4x^2+120x+680=0 | | -(5x+3)-(-4x-7)=7 | | X=4-20 | | 3x(4)= | | -24+2x=12-x | | 10x+6 = +6x+34 | | -(5x+3)-(4x-7)=7 | | 8(x+6)=8x+6 | | -4x8 | | -7+5r=-3(-1-5r) | | 45=m+9 | | -6+-6+-6= | | 5(-3k-6)=-3(4+k)+6k | | 9=6x | | 25-(-3c)=36 | | -1.8+-1.8+1.8+1.8= | | 3(x+2)=4(x+1)=2 |

Equations solver categories